Focus Group Playing Program: Meningkatkan Daya Imajinasi Melalui Media Bermain Serta Visual pada Usia Taman Kanak-Kanak - Arthur Huwae; Ketrin Putri Djasmita; Eunike Ivana Hartantio; Militya Christy Melalondo; Anggela Meilinda; Felly Zefanya Lasamahu; Kristalin Rumengan; Gloria Kumaat Monintja; Felani Omie Timpal; Putri Ivana Kezia Tamon; Zefanya Mikha Hombokau; Briany Julian Putri Wahyu; Galdies Betsi Lembang; Aneta Larasati Gondokusumo (AWLADY : Jurnal Pendidikan Anak, 2023)
The kindergarten learning system has many changes according to the curriculum by the government. These changes have an impact on the psychological development of children in participating in learning activities in class. The risks that arise cause the ability of imagination to be hampered and the learning process becomes ineffective. For this reason, it is necessary to have a program that can increase the imagination ability of kindergarten students, one of which is a Focus Group Playing Program. The purpose of this research was to determine the effectiveness of a program to improve the imagination ability of kindergarten students. A quantitative experiment with a one-group pretest-posttest design was used as the research method. The participants involved were 15 kindergarten students using the saturated sampling technique. This research consists of a Focus Group Playing Program module and an observation sheet for measuring the pretest-posttest score of imagination ability. The research data analysis method used the Wilcoxon Signed Rank Test. The results of this research proved that the focus group playing program effectively increases the imagination ability of kindergarten students (Z = 3.873 and sig. = 0.000). This research indicates that increasing the capacity of imagination helps students in their growth and development age. This is inseparable from the vital role of the ocus Group Playing Program that was implemented.